Sex differences in plasma metabolites in a guinea pig model of allergic asthma - Barosova, R; Baranovicova, E; Adamcakova, J; Prso, K; Hanusrichterova, J; Mokra, D (Physiological research, 2023)
Sex seems to be a contributing factor in the pathogenesis of bronchial asthma. This study aimed to find sex-related differences in metabolome measured by hydrogen-1 nuclear magnetic resonance ((1)H NMR) spectroscopy in healthy and ovalbumin (OVA)-sensitized guinea pigs. Adult male and female animals were divided into controls and OVA-sensitized groups. OVA-sensitization was performed by OVA systemic and inhalational administration within 14 days; on day 15, animals were killed by anesthetic overdose followed by exsanguination. Blood was taken and differential white blood cell count was measured. Left lung was saline-lavaged and differential cell count in the bronchoalveolar lavage fluid (BALF) was measured. After blood centrifugation, plasma was processed for (1)H NMR analysis. Metabolomic data was evaluated by principal component analysis (PCA). Eosinophil counts elevated in the BALF confirming eosinophil-mediated inflammation in OVA-sensitized animals of both sexes. Sex differences for lactate, glucose, and citrate were found in controls, where these parameters were lower in males than in females. In OVA-sensitized males higher glucose and lower pyruvate were found compared to controls. OVA-sensitized females showed lower lactate, glucose, alanine, 3-hydroxy-butyrate, creatine, pyruvate, and succinate concentrations compared to controls. In OVA-sensitized animals, lactate concentration was lower in males. Data from females (healthy and OVA-sensitized) were generally more heterogeneous. Significant sex differences in plasma concentrations of metabolites were found in both healthy and OVA-sensitized animals suggesting that sex may influence the metabolism and may thereby contribute to different clinical picture of asthma in males and females.
Keywords: Asthma; bronchiální astma; Allergens; Female; Bronchoalveolar Lavage Fluid; myši inbrední BALB C; pyruváty; alergeny; zvířata; myši; glukosa; Guinea Pigs; Pyruvates; Mice; Ovalbumin; ženské pohlaví; Male; laktáty; bronchoalveolární lavážní tekutina; Sex Characteristics; Glucose; morčata; pohlavní dimorfismus; Animals; mužské pohlaví; ovalbumin; Disease Models, Animal; Lactates; Mice, Inbred BALB C; modely nemocí na zvířatech